Growth of Lethal Violence in Brazil 2000–2017: A Space-Temporal Analysis of Homicides - Aransiola, Temidayo James (Journal of contemporary criminal justice, 2022)
This study investigates the space-temporal growth of homicide rates in Brazil from 2000 to 2017 and identifies determinants of the country’s growth of homicide rates. Data from the Brazilian Information System on Mortality and Censuses are used to estimate growth models combined with spatial statistics and Geographical Information Systems (GIS). Findings show evidence of change in the geographical distribution of lethal violence over time, characterized by a steady increase in the North and Northeast regions and a reduction in growth in the South and Southeast regions of Brazil. Social disorganization factors namely deprivation, ethnic heterogeneity, and urbanization are significant positive determinants of the growth of homicide rates. The results show a reduction of the predictive strength of income inequality and an increase in that of unemployment from the year 2010 to 2017. The theoretical and policy implications of these results are discussed.